Using a Pore-Scale Modelling Approach to Study Solute Dilution Process through Cemented Porous Media. (25th October 2022) - Hou, Yusong; Hu, Bill X.; Liu, Su; Xin, Hu; Wu, Jichun
Abstract : In this study, a pore-scale simulation method is applied to quantitatively study the variation of solute dilution through porous media with different cementation degrees and explore the corresponding mechanisms. The study results indicated that the cementation degrees of the solid grains had a significant effect on the solute dilution process and that the influence was very complicated. The complexity was manifested in that the effect of rising cementation degree on the solute dilution process would be different or even completely opposite in the porous media in which the solid grains cement slightly with that in porous media with a higher cementation degree. For example, for the porous media in which the solid grains were slightly cemented (the percentage of the cemented solid grains P c is less than 40%), the dilution effects became enhanced with the increase of cementation degree. Then, after P c increased to about 55%, the dilution effect was obviously weakened, and the solute was in an incomplete dilution state for a long period of time. In addition, this study found that the properties of the flow fields may vary greatly in porous media with different cementation degrees and that those differences in the flow fields resulted in the distinct behavior of the solute dilution. It is interesting to note that a more heterogeneous flow field had not necessarily led to the enhancement of the dilution process.